EFEKTIVITAS PENERAPAN KEBIJAKAN RESTRUKTURISASI DALAM MENGATASI PEMBIAYAAN BERMASALAH DI PT. BANK MUAMALAT INDONESIA TBK. KCP KOLAKA - Husnul Khatimah; Kasmiah Kasmiah (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
In the current era of globalization, many people have used this credit loan to help their lives. However, in terms of payments that must be paid by the customer at the time agreed upon by the bank, there are often arrears. This causes bad credit. Bad credit or non-performing financing is a common problem in the banking world. This can be seen from the many ways of handling non-performing financing. One of them is restructuring. The formulation of the problem in this research is what factors cause problem financing, how is the implementation of restructuring policy in overcoming problem financing, and how is the effectiveness of implementing restructuring policy in overcoming problematic financing at PT. Bank Muamalat Indonesia Tbk. KCP Kolaka? The research objectives are to find out what factors cause problem financing, to know the implementation of restructuring policies in overcoming Problem Financing, and to find out how effective the implementation of restructuring policies in overcoming problematic financing at PT. Bank Muamalat Indonesia Tbk. KCP Kolaka. The research method used includes qualitative research with a descriptive approach, this research was conducted at the office of Bank Mamalat Kcp Kolaka from October to December. The data sources are managers and employees as primary data and documents from Bank Muamalat as secondary data, using interview and documentation data collection techniques. The collected data is analyzed and then concluded to facilitate the reader. The results of this study indicate that financing problems are caused by two factors, the bank's internal factors and the customer's external factors. The policy of providing restructuring for problematic customers is given when the customer is in a 2C collectibility condition, namely the substandard class, where the customer has failed to pay for three months. The effectiveness of the implementation of this restructuring is very effective. This can be seen from the history of customers in helping customer problems.